Optimal use of recombinant factor VIIa in the control of bleeding episodes in hemophilic patients - John Puetz (Dove Medical Press, 2010)
John PuetzSaint Louis University, Department of Pediatrics, St Louis, Missouri, USAAbstract: One of the last remaining clinical hurdles in the treatment of people with hemophilia is the development of inhibitors. Alloantibodies or autoantibodies directed at coagulation factors render the infusion of coagulation factor concentrates ineffective, and alternative means must be used to achieve hemostasis. Recombinant factor VIIa (rFVIIa) was developed to control bleeding episodes in hemophilic patients with inhibitors. Clinical efficacy in achieving hemostasis in inhibitor patients was demonstrated by a compassionate-use protocol, as well as in randomized controlled trials. To date, over 1.5 million doses of rFVIIa have been given to inhibitor patients, with an excellent efficacy and safety record. Because of its short half-life, alternative means of dosing and infusing rFVIIa have been explored and are reviewed here.Keywords: hemophilia, inhibitor, recombinant, factor VIIa, inhibitors